Reliability, validity and performance determinants of the military simulation test for the assessment of anaerobic performance in soldiers - Helén, Joonas (2020)
Introduction: Measurements of physical fitness have been identified as one of the most important research priorities in the military. Currently, the physical fitness tests of The Finnish Defence Forces (FDF) do not include a valid and reliable anaerobic test. In order to develop job-related task simulation tests, the purpose of the study was to determine the reliability and validity of a high-intensity military simulation test (MST), which is designed to assess the task-specific anaerobic performance of soldiers. The MST includes typical combat-related maneuvers while wearing a 20 kg combat load.